Analysis and improvement of chemical pollution dispersion models in the environment - Kochanov , E. O. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2025)
Purpose. To develop and analytically substantiate a model for assessing the chemical situation during accidents at chemically hazardous facilities, taking into account the specific features of the formation of primary and secondary chemical contamination.Methods. The study uses an integrated analytical approach to modeling chemical contamination scenarios by applying modified atmospheric diffusion equations, formulas for calculating the mass of substance evaporation, the duration of cloud formation, and its spatial dispersion.Results. Special attention is paid to incorporating the roughness of the underlying surface, which affects the parameters of toxic cloud dispersion, and to determining the depth of impact zones depending on the type of hazardous substance, meteorological conditions, and site characteristics.The surface roughness parameter was introduced to account for terrain heterogeneity. Calculations were performed for various categories of hazardous substances (ammonia, chlorine) under typical conditions for Ukraine. Reference and regulatory data, as well as algorithms and scenarios from practical assessments of chemical situations, were used. Based on the developed model, calculations of the affected area for typical chemically hazardous facilities were performed; the penetration depth of toxic clouds was determined depending on the type of underlying surface, wind speed, and temperature. It was shown that accounting for roughness increases the accuracy of assessments by 12–18%, which is critical for operational decision-making. It was also established that the secondary cloud forms an additional risk zone, which under certain conditions may exceed the area of primary contamination. The model’s applicability for use in environmental monitoring and forecasting the consequences of man-made accidents was demonstrated.Conclusions. The proposed model allows for the consideration of topographic and meteorological factors in assessing chemical contamination. This improves the accuracy of determining the boundaries of affected zones and can be integrated into decision-support systems for rapid response by emergency services, environmental monitoring, and territorial planning under conditions of potential man-made hazards.